Throughput Analysis of WM-LEACH, LEACH, MH- LEACH and V-LEACH Protocol: a simulation based approach - Mahmuddin, Massudi; Alabadleh, W. A.; Kamarudin, L. M. (IOP Publishing, 2019)
This paper provides a passing description for some of routing protocols like LEACH, WM-LEACH, MH-LEACH and V-LEACH Protocol in Wireless Sensor Network (WSN) also a comparison study of these protocols based on one of performance matrices as throughput. Addition to this an attempt is done to calculate their throughput. The effect of these protocols are simulated through the MATLAB simulator. Finally, the throughput of the network increases with WM-LEACH with respect to send interval and number of bytes of data. In the WMLEACH, the throughput is higher than in other protocols which are compared in this research. This is because the WM-LEACH protocol reduces the communication cost between the domains by allowing more data in less time.-1.